# solve x4 17x2 16 0 let u

﻿

## Solve for x^4 17x^2 + 16 = 0 let u= Doubt Solutions

Solve for x^4 17x^2 + 16 = 0 let u= Solve each polynomial equation. 15. 15x^3119x^210x+16=0 16. x^314x^2+47x18=0 17. 5x^327x^217x6=0

## Solve x4 – 17x2 + 16 = 0. Let u

answers 46 dollars is the answer. stepbystep explanation: 6*6 = 36, 36+10=46 Solve x4 – 17x2 + 16 = 0. Let u = . allnswers...

## Solve x^4+17x^2+16=0, Microsoft Math Solver

Solve your math problems using our free math solver with stepbystep solutions. Our math solver supports basic math, prealgebra, algebra, trigonometry, calculus and more. x417x2+16=0 Four solutions were found : x = 4 x = 4 x = 1 x = 1 Step by step solution : Step 1 :Equation at the end of step 1 : ((x4) 17x2) + 16 = 0 Step 2 :Trying

## Solve by Factoring x^417x^2+16=0, Mathway

Solve by Factoring x^417x^2+16=0. Rewrite as . Let . Substitute for all occurrences of . Factor using the AC method. Tap for more steps... Consider the form . Find a pair of integers whose product is and whose sum is . In this case, whose product is and whose sum is .

## Solve x^417x^2+16=0, Microsoft Math Solver

Solve your math problems using our free math solver with stepbystep solutions. Our math solver supports basic math, prealgebra, algebra, trigonometry, calculus and more.

## Solved: Solve.x4 17x2 + 16 = 0, Chegg

Answer to Solve.x4 17x2 + 16 = 0. Video Guide for Intermediate Algebra (7th Edition) Edit edition. Problem 12E from Chapter 8.5: Solve.x4 17x2 + 16 = 0

## Solved: Solve 3(x + 4)2 + (x + 4) – 2 = 0 in two ways.(a

Solutions for Chapter 1.4 Problem 139E: Solve 3(x + 4)2 + (x + 4) – 2 = 0 in two ways.(a) Let u = x + 4 and solve the resulting equation for u. Then solve the iisolution for x.(b) Expand and collect like terms in the equation, and solve the resulting equation for x.(c) Which method is easier

## How do you solve x^418x^2+81=0, Socratic

Of course, we could use the quadratic formula or completing the square to solve this equation, but you''re usually not lucky enough to have a perfect square quadratic so take advantage. At this point, we have: #(u9)^2 = 0# To solve, we take the square root of both sides: #sqrt((u9)^2) = sqrt(0)# And this simplifies to #u9 = 0#